Absolute Farbe : Avantgarde 63. (Trier : Städtisches Museum Trier, 1963)
Bartels, Hermann ; Bemporad, Franco ; Berner, Bernd ; Busse, Hal ; Coviello, Peter ; Denny, Robyn ; Dienst, Rolf-Gunter ; Gaul, Winfred ; Greis, Otto ; Jochims, Reimer ; J_urgen-Fischer, Klaus ; Louis, Morris ; Micus, Eduard ; Pfahler, Georg Karl ; Quinte, Lothar ; Rainer, Arnulf ; Turnbull, William
Absolute Farbe : Avantgarde 63, Städtisches Museum Trier, 19. Juli bis 18. August 1963
Duits
kunstcatalogus